Müller cells and diabetic retinopathy. - Schellini, Silvana Artioli [UNESP]; Gregório, E. A.; Spadella, César Tadeu [UNESP]; Machado, J. L.; de-Moraes-Silva, M. A. (My University, 1995)
Müller cells provide nutrition for neural cells. We studied the structure and ultrastructure of Müller cells in the retina of thirty 3-month old Wistar rats, divided equally into 3 groups: normal rats, alloxan diabetic rats and treated alloxan diabetic rats, 1 and 12 months after induction of diabetes. We observed that the Müller cell nuclei under light microscope examination had hexagonal shape and higher density than the other nuclei. Differences between groups could be observed only by electron microscopy. In the diabetic rats, Müller cells presented dispersion of nuclear chromatin and electrondense nuclear granulations, with the presence of increased glycogen, dense bodies and lysosomes in the cytoplasm. The alterations were more frequent in the perivascular region and at 12 months. The treated diabetic rats exhibited some alterations we observed in diabetic rats, but these alterations were less intense. We conclude that, despite the treatment, the diabetic retinopathy continues to evolve.
Keywords: animal; diabetic retinopathy; experimental diabetes mellitus; glia; pathology; rat; retina; ultrastructure; Wistar rat; Animals; Diabetes Mellitus, Experimental; Diabetic Retinopathy; Neuroglia; Rats; Rats, Wistar; Retina